Environmental Provisions for Eurasian Economic Union’s RTAs - A. E. Kuznetsova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article considers environmental provisions in the EAEU-Viet Nam FTA as well as trade agreements signed by countries currently involved in FTA negotiations with the Eurasian Economic Union. The author analyzes the prospects and viability of the inclusion of broad environmental provisions in the future RTAs of the EAEU and concludes that, due to the lack of significant empirical data on their efficiency, it will be viable only if all parties are strongly committed to their implementation. In other cases, the EAEU members might want to focus on protecting their right to regulate and creating efficient mechanisms for environmental cooperation.